Pengaruh Ukuran Komisaris dan Komisaris Independen Terhadap Return on Equity pada Perusahaan BUMN yang Melakukan Holding - Simbolon, Ramadona (Universitas Islam Islam Sumatera Utara, 2024)
This study aims to examine the influence of the size of the board of commissioners (UKOM) and independent commissioners (KOMID) on Return on Equity (ROE). The population of this study consists of all state-owned enterprises (BUMN) that are engaged in holding. The sample size of this study is 47 state-owned enterprises (BUMN) selected using purposive sampling, with the criteria being BUMN that have officially formed a holding based on the Minister of BUMN's Decision or similar regulations, published complete and accessible annual reports during the period 2020–2023, and have information related to the structure of the board of commissioners as well as the financial performance indicator ROE. The research results reveal that the size of the board of commissioners does not affect ROE. However, this research also revealed an important finding that the size of independent commissioners has a positive and significant impact on ROE. The government needs to play an active role in maintaining the objectivity and independence of commissioners, so they are protected from political intervention. This is important to ensure the effectiveness of oversight on company operations, evaluation of strategic policies, and compliance with the principles of good corporate governance.